2010
DOI: 10.1029/2009wr008336
|View full text |Cite
|
Sign up to set email alerts
|

Scaling frequency of channel‐forming flows in snowmelt‐dominated streams

Abstract: 1] The scaling properties of channel-forming flows are investigated using a regional flow frequency model developed for snowmelt-dominated streams in Colorado. The model is derived from analyses of daily flow records at 32 gauging stations where we have independent measurements of the bankfull discharge. The study sites are located in alpine/subalpine basins with drainage areas ranging from 4 to 3700 km 2 . The frequency distribution of daily flows at these locations can be reproduced with a broken power law (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…Q brk also increases with basin area A (Fig. 3b) as was shown by Segura and Pitlick (2010) who describe F Q = f(Q) and Q brk by broken power law functions.…”
Section: Revised Computation Of Flow Frequency Distributionssupporting
confidence: 52%
See 3 more Smart Citations
“…Q brk also increases with basin area A (Fig. 3b) as was shown by Segura and Pitlick (2010) who describe F Q = f(Q) and Q brk by broken power law functions.…”
Section: Revised Computation Of Flow Frequency Distributionssupporting
confidence: 52%
“…Differences in Q eff by a few flow bins are attributable to irregularities in the flow frequency data. Results obtained for Q eff in this study are also expected to be unchanged if F Q = f(Q) is expressed by a broken power law function (Segura and Pitlick, 2010).…”
Section: Effects Of Flow Frequency Distribution Typementioning
confidence: 89%
See 2 more Smart Citations
“…The selection was achieved using a greedyheuristic search process, which searches for a global optimal solution by finding locally optimal solutions. The selection of DA is consistent with results of other studies that demonstrated the relevance of DA as a major hydrologic scaling parameter, especially for peak and annual flows (e.g., Gupta et al, 1994;Vogel and Sankarasubramanian, 2000;Ogden and Dawdy, 2003;Furey and Gupta, 2005;Segura and Pitlick, 2010). The drainage area, which controls the scale of exchange and interaction between climatic and watershed processes, was selected for all 19 percentiles; the HSI, which is a measure of the control of water movement through the soil matrix (drainage potential), was selected for 10 of the 19 percentiles; and the RF1, which is a measure of extreme climatic events, was selected for 7 of the 19 percentiles.…”
Section: Journal Of the American Water Resources Associationsupporting
confidence: 89%